Emphasis of Homoeopathic Pharmacy for BHMS Students (Homoeopathy for All, 2025)
Homeopathy was introduced in India  the early 19th century. It flourished  in Bengal at first, and then spread  all over India. In the beginning, the  system was extensively practised by  amateurs in the civil and military  services and others. Mahendra Lal  Sircar was the first Indian who  became a homeopathic physician. A  number of allopathic doctors started  homeopathic practice following  Sircar's lead. The ‘Calcutta  Homeopathic Medical College’, the  first homeopathic medical college  was established in 1881. This  institution took on a major role in  popularising homeopathy in India.
Keywords: flourished; Bengal; extensively; amateurs